Marital satisfaction of dual-earner Muslims in Malaysia : the influence of negative affectivity, marital stress and religious coping - Rozaina Zainul Abidin (Kulliyyah of Education, International Islamic University Malaysia, 2021)
The present study was conducted with several objectives; to construct-validate the measurement model of marital satisfaction, to estimate the causal relations between negative affectivity, marital stress, religious coping and marital satisfaction in the postulated model and to explore the likelihood of moderation effect of gender as well as length of marriage in the model. A total of 585 dual-earner married Muslims in Selangor, Malaysia (293 females and 292 males) were drawn from a stratified sample randomly. A set of questionnaires were developed to collect data; the first part covered the demographic information of the respondents and the remaining consisted of questionnaires with 33 items, rated on 7-Likert type categories, adapted from four established scales which have been validated and used in previous studies. The instrument went through extant literature and content validation process which involved 15 experts in the areas of marriage and family counselling as well as scale development. Data were analysed using descriptive statistics, Principal Axis Factoring (PAF), Confirmatory Factor Analysis (CFA) and Structural Equation Modeling (SEM) procedures. The results indicated that the research instrument was reliable and psychometrically sound. It also confirmed the unidimensional structure of each constructs of interest and the adequacy of the model. The study found that religious coping and marital stress influenced the marital satisfaction of dual-earner Muslims. However, negative affectivity was not found to exhibit statistically significant relationship with marital satisfaction. The results also showed that religious coping mediated the relationship between negative affectivity and marital satisfaction. Although marital stress was found to exhibit a statistically significant effect on marital satisfaction, their relationship was neither significant nor important through the mediation path of religious coping. Finally, the test of moderation revealed that gender did not moderate the path coefficient between religious coping and marital satisfaction among dual-earner Muslims, while length of marriage was significant in moderating this relationship. The study has validated the marital satisfaction model of Muslim dual-earner marriages and offered new insights on the interrelationships between the studied variables, in light of the current challenges faced by married dual-earner Muslims living in the modern world. Last but not least, theoretical and practical implications of these findings and recommendations for authority bodies, pre and post marital education as well as helping professionals were discussed.